Berekonomi Untuk Hidup Layak - Herman, Muhammad Akbar; Ridwan, Muhammad Saleh; Lutfi, Mukhtar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this research is to understand the Principles of Economics in Islam and the Concept of Decent Living in Islam. The results of this research show: 1) The definition of Islamic economics in the scientific literature includes several perspectives from experts, but substantively, Islamic economics is a science that studies human behavior in efforts to meet needs with limited resources within the framework of Sharia. Another definition formulates that Islamic economics is a science that studies the behavior of a Muslim in an Islamic society framed by Sharia. The principles of Islamic economics, which form the structure of Islamic economics, are based on five universal values, namely: tauhid (faith), 'adl (justice), nubuwwah (prophethood), khilafah (government), and ma'ad (result); 2) Islamic economics, which is part of Islamic law, naturally has goals that cannot be separated from the main objectives of Islamic law. The main goal of Islamic economics is to achieve human objectives of attaining happiness in this world and the hereafter (falah) and a good and honorable life (al-hayah al-thayyibah). This is the definition of welfare in the Islamic approach, which is certainly different from the concept of welfare in traditional secular and materialistic economics.